Function Addition of Silk to Silk Clearance for Power PCB Design using User- Menu Features on Zuken CR-5000 - Muhamad Fadli; Nugroho Widianto (Peneliti.net, 2023)
The use of Printed Circuit Board (PCB) must never be missed in electronics field because its pivotal function as the connector of electrical terminals or leads. Thus, PCB design has to be made properly to create functions that are precise to the system designed. Almost every electronic device manufactory uses machine or robot for fabrication. Each manufactory has their own rule check for fabrication (Manufacture Rule Check) that should be implemented to maintain the run of production process well without error. One of the error check process that is advanced now is using user menu feature on Zuken CR-500 application used by Samsung Electro Mechanic South Korea company. Not every error check using user menu can fulfill the whole design rule check determined by the industry, with the development of this user menu feature, it is hoped can handle the undergone error check. The distance between components assembled using machine or robot has minimum clearance rule that is 1mm. Adding functions on user menu feature can detect the error when the distance between the components does not correspond to the determined standard. According to the conducted research result, user menu function can be added to check the distance between components well. By viewing contents of command on environment feature, the syntax of executed actions while the process of designing can be seen. Briefly, the system flow is to make log file saved in certain directory that is later called by adding user menu button and taking the data from the log file made